The Effect of Using Liquid Latex as an Additive in Asphalt Concrete–Wearing Course (AC-WC) Mixtures on Marshall Characteristics - Nadya Shafira Salsabilla; Weimintoro Weimintoro; Muhamad Yusuf; Teguh Haris Santoso (Lembaga Pengembangan Kinerja Dosen, 2026)
Population growth and increasing economic activities have raised the demand for durable and high-quality road infrastructure. However, the Asphalt Concrete–Wearing Course (AC-WC), which functions as the surface layer of flexible pavements, often suffers from premature damage such as cracking and deformation due to heavy traffic loads and extreme weather. Therefore, improvements in asphalt mixture materials are necessary. One alternative is the use of liquid latex derived from natural rubber as an additive. Owing to its high elasticity, liquid latex is expected to improve flexibility, crack resistance, and durability of asphalt mixtures. This study aims to evaluate the effect of liquid latex addition on the Marshall characteristics of AC-WC mixtures and to determine the optimum latex content. The research employed laboratory experimental methods using liquid latex contents of 0%, 2.5%, 5%, 7.5%, and 10%, with three specimens prepared for each variation. The evaluated parameters included stability, flow, air voids in the mix (VIM), voids in mineral aggregate (VMA), voids filled with asphalt (VFA), Marshall Quotient (MQ), and density. The results indicate that liquid latex significantly affects all Marshall parameters. However, excessive latex content reduces mixture performance. The optimum condition was achieved at 2.5% liquid latex with an asphalt content of 5.65%, producing a stability of 1102.2 kg, flow of 3.13 mm, VIM of 3.87%, VMA of 17.01%, VFA of 77.26%, MQ of 355.15 kg/mm, and density of 2.297 g/cc. All parameters satisfy the 2018 Bina Marga General Specifications (Revision 2).